Efficacy and Safety of Mirror Therapy for Post-stroke Dysphagia: A Systematic Review and Meta-Analysis - He, Kelin; Wu, Lei; Ni, Fengjia; Li, Xinyun; Liang, Kang; Ma, Ruijie (Frontiers in Neurology, 2022)
Background Post-stroke dysphagia is a common symptom after stroke and one of the most frequent and severe complications of stroke. Over the recent years, mirror therapy has generated significant research interest as a non-invasive therapeutic and rehabilitative intervention for post-stroke dysphagia and has been investigated in several randomized controlled trials in single center. Objective In this study, we aimed to evaluate the efficacy and safety of mirror therapy for post-stroke dysphagia. Methods A total of seven databases were searched comprehensively from inception to the 31 December 2021, including PubMed, the Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Service System (SinoMed), Wan-fang database, and the Chinese Scientific Journals Database (VIP) from inception to 31 December 2021. The primary outcome measure was efficacy, as measured by clinical effectiveness rate. Secondary outcomes included the water swallowing test and the incidence of pneumonia. In addition, we applied the Cochrane Risk of Bias Tool to investigate the risk of bias. Potential publication bias was evaluated by applying Egger's bias indicator test and by assessing the symmetry of data when visualized as funnel plots. Results A total of five randomized controlled trials (135 subjects in the experimental group and control group) were found to report the application of mirror therapy for post-stroke dysphagia and were included in this study. No publication bias was detected. Meta-analysis revealed that mirror therapy had a positive effect on the rate of clinical efficacy [odds ratio (OR) = 4.22; 95% confidence interval (CI): 2.3–7.73] and the water swallowing test [mean difference (MD) = −0.76; 95% CI = −1.29 to −0.22]. Moreover, mirror therapy reduced the incidence of pneumonia (OR = 0.13; 95% CI = 0.03–0.49). Subgroup analyses indicated that mirror therapy during the acute phase was robust but was unstable during the convalescent phase. Sensitivity analysis revealed that the results generated by our meta-analysis were robust and stable. Conclusions Available evidence appears to suggest that mirror therapy may have a role in the management of post-stroke dysphagia but has yet to be fully confirmed. Existing evidence from clinical trials suggests that evidence relating to the safety of mirror therapy for patients with post-stroke dysphagia is not yet sufficient. Systematic Review Registration Identifier: CRD42022302733.